Distribution of alpha1 antitrypsin rare alleles in six countries: Results from the Progenika diagnostic network - Lopez-Campos, José Luis; Rapun, Noelia; CZISCHKE LJUBETIC, KAREN NICOLE; Jardim, José R.; Acquier, Mariano Fernandez; Munive, Abraham Ali; Günen, Hakan; Drobnic, Estrella; Miravitlles, Marc; Osaba, Lourdes (My University, 2023)
Background: Knowledge of the frequency of rare SERPINA1 mutations could help in the management of alpha1 antitrypsin deficiency (AATD). The present study aims to assess the frequencies of rare and null alleles and their respiratory and hepatic pathogenicity. Methods: This is a secondary analysis of a study that evaluated the viability of the Progenika diagnostic genotyping system in six different countries by analyzing 30,827 samples from cases of suspected AATD. Allele-specific genotyping was carried out with the Progenika A1AT Genotyping Test which analyses 14 mutations in buccal swabs or dried blood spots samples. SERPINA1 gene sequencing was performed for serum AAT-genotype discrepancies or by request of the clinician. Only cases with rare mutations were included in this analysis. Results: There were 818 cases (2.6%) carrying a rare allele, excluding newly identified mutations. All were heterozygous except for 20 that were homozygous. The most frequent alleles were the M-like alleles, PI*Mmalton and PI*Mheerlen. Of the 14 mutations included in the Progenika panel, there were no cases detected of PI*Siiyama, PI*Q0granite falls and PI*Q0west. Other alleles not included in the 14-mutation panel and identified by gene sequencing included PI*Mwürzburg, PI*Zbristol, and PI*Zwrexham, and the null alleles PI*Q0porto, PI*Q0madrid, PI*Q0brescia, and PI*Q0kayseri. Conclusions: The Progenika diagnostic network has allowed the identification of several rare alleles, some unexpected and not included in the initial diagnostic panel. This establishes a new perspective on the distribution of these alleles in different countries. These findings may help prioritize allele selection for routine testing and highlights the need for further research into their pathogenetic role.
Keywords: alpha1 antitrypsin deficiency; diagnosis; frequency; null alleles; rare alleles; alleles; alpha 1-antitrypsin; alpha 1-antitrypsin deficiency; genotype; heterozygote; humans; mutation; alpha 1 antitrypsin; alpha 1 antitrypsin; adult; aged; alpha 1 antitrypsin deficiency; article; buccal swab; controlled study; dried blood spot testing; gene frequency; gene mutation; gene sequence; genetic association; genotyping; heterozygosity; homozygosity; human; human tissue; liver; major clinical study; middle aged; null allele; pathogenicity; respiratory system; secondary analysis; very elderly; young adult; allele; alpha 1 antitrypsin deficiency; genetics; genotype; heterozygote; mutation